Leveraging Crowdsourcing for Fan-Driven Content Creation in Sports: Enhancing Engagement and Innovation - Yue Man; Syamsul Bahrin Bin Zaibon; Yangzi Hu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The digital revolution and the rise of social networks have transformed how content is created within the sports industry, shifting towards more fan-driven approaches. This paper explores the dynamics of crowdsourcing in the sports sector, analyzing how market influences and governmental guidance shape the diversification of content production. Through case studies, we examine various forms of public participation in sports media, highlighting how fans are not just consumers but active contributors to the content ecosystem. This research aims to deepen understanding of the role of fans in shaping sports media and to assess the effectiveness of crowdsourcing as a strategy for enhancing fan engagement and content innovation. By exploring these participatory mechanisms, we provide insights into how sports organizations can harness the power of crowdsourcing to foster a more engaged fan base and drive content creativity. The findings offer practical implications for sports media producers seeking to leverage digital platforms and fan input to innovate and expand their content offerings.